Brand network communities: Leveraging brand relationships within the supply-chain. Issue 6 (November 2017) - Hawkins, Matthew
Abstract Forming and managing a brand community is now a common marketing strategy for brands looking to increase consumer commitment and financial performance. Despite the advantages of having a strong brand community, brand community management is traditionally directed toward the consumer or end-user. The purpose of this paper is to argue brand communities can and should be formed within a brand's entire network or supply-chain. Brand network community marketing is a user-centric marketing perspective. It purposefully encourages and supports the formation of brand communities with brand users regardless of their location within the supply-chain. In order to develop a brand community within a brand's network, four activities to focus on are offered. The article concludes by discussing the implications of this work and offering avenues for future research.